Usual vulval intraepithelial neoplasia in HIV-positive women – a case series. (December 2016) - Toby, M; Conway, K; Sethi, G; Lewis, F
Usual or undifferentiated type vulval intraepithelial neoplasia (VIN) is more common in young women and is usually associated with high-risk human papillomavirus infection. It is associated with the development of basaloid or warty squamous cell carcinoma. Studies have shown that HIV-positive women have an increased risk of VIN and invasive vulval carcinoma, but there is a paucity of data about this cohort of women. The objective of this study was to describe the clinical features and treatment responses of HIV-positive women diagnosed with VIN in a specialist vulval dermatology clinic. HIV-positive women diagnosed with VIN from 2007 to 2013 were retrospectively identified. Data were collected on demographics, clinical features, treatments and outcomes. Seven cases were retrospectively identified. The median CD4 cell count at presentation was 500 cells/mm 3 (range 59–761). Five had multifocal VIN. Five were treated with imiquimod alone, one had surgical excision and one patient was treated with imiquimod and surgery. Five of the seven had complete resolution of disease. HIV-positive patients with VIN had good responses to treatment with imiquimod. They were likely to be stable on combination antiretroviral therapy at presentation, have multifocal disease and concurrent vaginal, anal or cervical intraepithelial neoplasia.